Catecholaminergic depletion in nucleus accumbens enhances trace conditioning - Nelson, Andrew J.D.; Thur, Karen E.; Spicer, C.; Marsden, C.A.; Cassaday, Helen J. (De Gruyter Open, 2011)
Purpose: To examine the effect of dopamine depletion in nucleus accumbens on trace conditioning; to distinguish the role of core and shell sub-regions, as far as possible. Material/Methods: 6-hydroxydopamine was used to lesion dopamine terminals within the core and shell accumbens. Experiment 1 assessed conditioning to a tone conditioned stimulus that had previously been paired with footshock (unconditioned stimulus) at a 30s trace interval. Experiment 2 subsequently assessed contiguous conditioning (at 0s trace) using a light conditioned stimulus directly followed by the unconditioned stimulus.